(untitled) (Modern education and development, 2025)
At present, there are a large number of various methods of laboratory diagnostics of tuberculosis, to a greater or lesser extent reflecting the peculiarities of the course of the pathological process. General clinical, biochemical, immunological, bacteriological studies provide clinicians with the most accurate and reliable information about the state of the internal environment of the patient’s organism and the course of vital processes, help to adequately judge the presence or absence of a pathological condition, its dynamic changes, and the effectiveness of treatment [1,2,3,4,5].